Macromedia Flash professional 8 game development - Glen Rhodes (Charles River Media, 2007)
Written by a professional game developer, this book details the actual science of game development, including design, story character development, the physics and motion of a game, and audio issues. In this new edition, all of the latest features of Flash Professional 8 are covered, including the new sound channels, bitmap caching, texture pages, and more. The book also focuses on the incredible power of the new BitmapData class, and how it can be used to take the performance of Flash games to a whole new level. Through the book a variety of games are created using the power of Flash and the most recent advancements in ActionScript. Beginning with the basics of design, the book progresses through the entire process to teach programmers and Web developers how to create professional quality games quickly. With a basic knowledge of Flash and the techniques provided here, developers will be able to enhance their productivity and produce high quality games that make a real impact